Optimising Bio-Fortified Compost for Effective Suppression of Soil-Borne Diseases and Boosting Tomato Yield - Mahmudul Sultan; Md. Khurshed Alam Bhuiyan; Md. Giashuddin Miah; Md. Abu Ashraf Khan; Shaikh Sharmin Siddique; Md. Tanbir Rubayet (Future Science, 2026)
Soil-borne fungal pathogens are a major constraint in tomato cultivation, often causing severe yield losses. This study aimed to optimise the dosage of Trichoderma-fortified compost (TFC) as an eco-friendly strategy for disease management and growth promotion. The antagonistic potential of Trichoderma harzianum isolate PABT-22 (TP-22) was validated in vitro, showing >90% inhibition against Fusarium oxysporum f. sp. lycopersici (Fo), Sclerotium rolfsii (Sr), and Rhizoctonia solani (Rs). The most effective isolate was incorporated into poultry manure compost and tested in field experiments with eight treatments, including five TFC dosages (100–500 g per 6 m² plot). All TFC treatments significantly improved plant growth compared with controls, with the greatest benefits recorded in T8 (500 g per plot ≈ 833 kg ha⁻¹). In T8 plots, disease incidence was reduced to 12.5% for Fusarium wilt and southern blight and 14.0% for Rhizoctonia root rot, compared with high incidence in pathogen-only controls. Yield increased by 27.3% (Fo), 29.6% (Sr), and 29.1% (Rs) under T8. These results confirm that a standardised dose of 500 g TFC per plot provides effective pathogen suppression and substantial yield, supporting its adoption as a low-cost, sustainable solution for tomato production.